Hypothetical ratings of coronary angiography appropriateness: are they associated with actual angiographic findings, mortality, and revascularisation rate? The ACRE study. Issue 6 (1st June 2001) - Hemingway, H; Crook, A M; Banerjee, S; Dawson, J R; Feder, G; Magee, P G; Wood, A; Philpott, S; Timmis, A
Abstract : OBJECTIVE: To determine whether ratings of coronary angiography appropriateness derived by an expert panel on hypothetical patients are associated with actual angiographic findings, mortality, and subsequent revascularisation in the ACRE (appropriateness of coronary revascularisation) study. DESIGN: Population based, prospective study. The ACRE expert panel rated hypothetical clinical indications as inappropriate, uncertain, or appropriate before recruitment of a cohort of real patients. SETTING: Royal Hospitals Trust, London, UK. PARTICIPANTS: 3631 consecutive patients undergoing coronary angiography (no exclusion criteria). MAIN OUTCOME MEASURES: Angiographic findings, mortality (n = 226 deaths), and revascularisation (n = 1556 procedures) over 2.5 years of follow up. RESULTS: The indications for coronary angiography were rated appropriate in 2253 (62%) patients. 166 (5%) coronary angiograms were performed for indications rated inappropriate, largely for asymptomatic or atypical chest pain presentations. The remaining 1212 (33%) angiograms were rated uncertain, of which 47% were in patients with mild angina and no exercise ECG or in patients with unstable angina controlled by inpatient management. Three vessel disease was more likely among appropriate cases and normal coronaries were more likely among inappropriate cases (p < 0.001). Mortality and revascularisation rates were highest among patients with an appropriate indication, intermediate in those with an uncertain indication, and lowest in the inappropriate group (log rank p = 0.018 and p < 0.0001, respectively). CONCLUSION: The ACRE ratings of appropriateness for angiography predicted angiographic findings, mortality, and revascularisation rates. These findings support the clinical usefulness of expert panel methods in defining criteria for performing coronary angiography.